E-Commerce applications using Oracle8i and Java from scratch - Thakkar, Meghaj (Prentice Hall New Delhi, 2000)
A reference for networking professionals and power users who need answers fast, this volume teaches you how to optimize the Windows 2000 system for the most efficient performance based on your specific work habits. Within the pages of this book you will find everything you need to solve your problems in a clear and direct way.